Investigation of Antibiotic Resistance Patterns and Reduced Vancomycin Susceptibilities of Methicillin-Resistant Staphylococcus aureus Isolates: A Multi-Center Study - SÜMBÜL, BİLGE; Cikman, Aytekin; Aydin, Merve; Gulhan, Baris; Parlak, Mehmet; Gultepe, BİLGE; Kalayci, Yildiz; BILMEN, Fulya Bayindir; Solmaz, Sinem; Ozekinci, Tuncer (My University, 2015)
The aims of this study were to determine the minimum inhibitory concentration (MIC) values of vancomycin, teicoplanin, daptomycin, quinupristin/dalfopristin, linezolid, tigecycline, chloramphenicol, rifampicin, ofloxacin and tetracycline and to investigate the reduced vancomycin susceptibility among methicillin-resistant Staphylococcus aureus (MRSA) strains isolated in hospitals located in different geographical regions of Turkey. A total of 100 MRSA strains isolated from patients (of which 50% were from intensive care units) hospitalized in seven centers in Turkey [Istanbul (n= 15), Ankara (n= 15), Izmir (n= 15), Adana (n= 15), Diyarbakir (n=15), Erzincan (n= 15), Van (n= 10)], between August 201 3 August 2014, were included in the study. Fourty-three strains were isolated from blood, whereas 21 were from lower respiratory tract, 17 from wounds, eight from catheters, six from urine, four from nasal swab and one from cerebrospinal fluid samples. Methicillin resistance of the isolates was determined by using cefoxitin (30 mu g) disk with standard disk diffusion method, while the MIC values of other antibiotics were determined with E-test in accordance with the recommendations of Clinical and Laboratory Standards Institute (CLSI). MIC results obtained for quinupristin-dalfopristin (Q/D) were evaluated according to the CLSI criteria used for methicillin-susceptible S.aureus and for tigecycline according to the criteria recommended by the Food and Drug Administration for MRSA. Primarily, agar screening method (ASM) was used for determination of vancomycin-intermediate S.aureus (VISA) and heterogeneous VISA (hVISA) strains. Brain heart infusion agar containing 6 mu g/ml vanconnycin was used in ASM, and the strains with suspicion of VISA/hVISA were screened by standard E-test and macro E-test methods. All MRSA strains were susceptible to vancomycin, teicoplanin, daptomycin, Q/D and linezolid by E-test method; and their rates of susceptibility for tigecycline, chloramphenicol, rifampicin, ofloxacin and tetracycline were detected as 89%, 97%, 40%, 39% and 32%, respectively. MIC50/MIC90 values were 1.5/2 mu g/ml for vancomycin, 2/4 mu g/ml for teicoplanin, 0.19/0.38 mu g/ml for daptomycin, 0.19/0.38 mu g/ml for Q/D, 0.75/1 mu g/ml for linezolid, 0.19/0.75 mu g/ml for tigecycline, 3/6 mu g/ml for chloramphenicol, 32/32 mu g/ml for rifampicin, 32/32 mu g/ml for ofloxacin and 32/64 mu g/ml for tetracycline, respectively. For the evaluation of reduced vancomycin susceptibility, 2% (2/100) of MRSA strains were defined as VISA and 5% (5/100) as hVISA with ASM. One of those seven isolates identified as VISA/hVISA with ASM was evaluated as suspected hVISA by using both standard E-test and macro E-test methods. In conclusion, no MRSA resistant strain to vancomycin, teicoplanin, daptomycin, Q/D and linezolid was determined in our study. However tigecycline resistance (11%) was found higher than expected. As the glycopeptide resistance is increasing in the world and because of the intense use of these drugs in Turkey, the rates of vancomycin resistance among MRSA strains should be investigated periodically.